Analisis Kompetensi, Tunjangan Kinerja dan Beban Kerja Terhadap Kinerja Pegawai dengan Kepuasan Kerja Sebagai Variabel Intervening - Maskuri Maskuri; Suyanto Suyanto (J-MAS (Jurnal Manajemen dan Sains), 2023)
The problem raised in this study is that there is still a gap between the competencies required to carry out duties in a position with the competence owned by employees, the number of employees who are still far from the ideal of the organization, the employees who do not do the absenteeism, the performance benefits provided have not been in accordance with the workload carried out by employees and the workload provided is not in accordance with the number of employees. Therefore, the researchers conducted a research with the aim to test the analysis of competencies, performance benefits and workloads owned by each personnel and test the level of employee job satisfaction used as a mediation variable (Intervening). This study used the data collection methods namely observations, questionnaires.